STRATEGI PRODUKSI, PEMASARAN, DAN PENGELOLAAN SDM NET.TV DALAM MENGHADAPI PERSAINGAN INDUSTRI TELEVISI - Hamid, Joni Arman (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2021)
Competition in the television industry in Indonesia is experiencing rapid development, especially now that the era of media convergence is expanding. NET TV as one of the national private companies is present with strategies, marketing, and Human Resources (HR) development by combining conventional methods with new ways. The writing of this paper is on program development concepts which include: pre-production, production, and evaluation. For marketing strategy, NET.TV reduces to Kotler and Keller who see marketing strategies starting from the target audience, consumer classification, and target market determination. This journal writing uses a qualitative approach, with a constructivist paradigm, and uses the case study method. The data was obtained through literature review, observation, and in-depth interviews with editors, HRD, Marketing, and NET.TV Head of Production. The results showed that NET.TV followed production procedures by relying on the creativity of human resources without deviating from the technical rules of production. Likewise, related to marketing, they utilize social media with human resource creativity.